Caracterización del desarrollo proyectado a nivel portuario y logístico en Cartagena para el período 2018-2022 (2021)
Internationally, the shipping and port industry has experienced an exponential growth, given among other reasons by the conclusion of trade agreements that stimulate economic exchange in different regions. Latin America and especially Colombia have not been unaffected by this development; on the contrary, they are a fundamental part of it. The different port cities in the country have stood out for their gradual but steady growth, including the city of Cartagena. The present project addresses a general characterization of the development at port and logistics level in Cartagena for the period 2018 - 2022, so three specific goals were developed, the establishment of the macro process of the company Grupo Puerto de Cartagena, the determination of trends in maritime transport and the description of the bets in the projected development in the company for 2018-2022. A qualitative, quantitative and descriptive approach research was carried out, which is defined as a study that serves to analyze how a phenomenon and its components are and how they are manifested. An analytical method is defined as a research method that consists of the dismemberment of a whole, breaking it down into its parts or elements to observe the causes, nature and effects.